INSTITUTIONAL LOGICS OF SUSTAINABILITY: AN EVALUATION OF KEY FACTORS IN THE CONTEXT OF KNOWLEDGE-BASED INSTITUTIONS - Zineb ZNAGUI (Management & Marketing)
Institutional Logics of Sustainability (ILS) comprise the principles, beliefs and norms that guide organizational behavior towards sustainable practices, reflecting societal and environmental values within institutions. Although the concept of institutional logic has been widely explored in organization theory, its specific application to sustainability, particularly within knowledge-based institutions (KBIs), remains under-examined. This study fills important gaps in the literature by identifying and conceptualizing the key factors that constitute KBIs, focusing on how KBIs, such as universities, research centers and technology companies, prioritize and implement sustainability within their organizational frameworks. Through a comprehensive analysis, the research examines the implications of ILS on organizational behavior and decision-making in KBIs. Findings highlight the critical role of regulatory environments, stakeholder expectations, organizational learning and industry-specific characteristics in shaping sustainability practices. This study contributes to a better understanding of the mechanisms governing sustainability in KBIs and offers valuable insights for practitioners and policy-makers wishing to advance sustainable development in these influential sectors.